Prevalence and Factors Associated with Intestinal Parasitic Infections among Pregnant Women in West Gojjam Zone, Northwest Ethiopia - Tadesse Hailu; Bayeh Abera; Wondemagegn Mulu; Simachew Kassa; Ashenafi Genanew; Arancha Amor (Journal of Parasitology Research)
Background. Intestinal parasitic infections are the major causes of morbidity and mortality in sub-Saharan countries. The disease burden of these parasites is significantly high among pregnant women in developing countries like Ethiopia. Poor living conditions, sanitation, and hygiene are believed to be the contributing factors. The aim of this study was to determine the magnitude of intestinal parasitic infection and factors associated with pregnant women. Methods. A cross-sectional study was conducted from February 2017 to June 2017. A structured questionnaire was used to obtain the sociodemographic and other explanatory variables via face-to-face interviews. Stool samples were collected and examined using formol ether concentration technique. The magnitude of parasitic infection was calculated using descriptive statistics. The association between intestinal parasitic infection and determinant factors was assessed by logistic regression. The differences were considered to be statistically significant if the p value was less than 0.05. Results. From a total of 743 pregnant women, the overall prevalence of intestinal parasitosis was 277 (37.3%). The prevalence of hookworm 138 (18.6%) was the leading cause of intestinal parasitosis followed by E. histolytica/dispar 113 (15.2%). Dwelling in rural area (AOR: 2.9 (95% CI: 1.85-4.85)), being a farmer (AOR: 1.91 (95% CI: 1.20-3.03)), eating raw vegetables (AOR: 1.45, 95% CI:0.09-0.24), lack of proper use of latrine (AOR: 2.89 (95%1.18-7.08)), poor environmental sanitation (AOR: 0.19 (95%: CI:0.08-0.47)), habit of soil eating (AOR: 0.42 (95% CI: 0.25-0.72)), having irrigation practice (AOR: 0.47 (95% CI: 0.29-0.77)), and lack of health education (AOR: 0.32 (95% CI: 0.13-0.77)) were significantly associated with intestinal parasitic infections. Conclusions. Intestinal parasitic infection is a major problem among pregnant women in the study area. High parasitic infection is associated with poor hygienic and sanitation practices. Therefore, awareness creation through health education should be given to pregnancy on intestinal parasitic infection and associated factors.